The effect of nanocrystalline microstructure on deuterium transport in displacement damaged tungsten - S. Markelj; T. Schwarz-Selinger; M. Kelemen; E. Punzón-Quijorna; J. Zavašnik; A. Šestan; D. Dellasega; G. Alberti; M. Passoni (Nuclear Materials and Energy, 2023)
The influence of grain boundaries (GBs) on the deuterium (D) transport and the creation of defects in nanocrystalline tungsten (W) films deposited on a W substrate was studied. Samples with three different grain sizes were produced for this purpose: a sample with a film having nanometer-size grains, a sample with hundred nanometer-grained film and a sample with micrometer-grained film. Samples were irradiated by 20 MeV W ions at 300 K to create displacement damage and exposed to 300 eV D ions at 450 K to populate the created and any pre-existing defects. The D transport and retention was assessed by measuring D depth profiles after certain exposure times by nuclear reaction analysis (NRA) using a 3He ion beam. From the final D concentration in the damaged area we could determine the concentration of defects that trap hydrogen, showing that the sample with the smallest grain size had the highest D concentration and it decreases with the increase of the grain size. Therefore, in nanocrystalline tungsten irradiated at 300 K, GBs do not improve radiation resistance, which would lead to fewer defects. For the first time, we show experimentally, that D transport is faster inside the nanometer-grained sample as compared to the micrometer-grained sample, meaning that D atoms have enhanced bulk diffusion along GBs. Accidentally, the film thickness was so thin that the W irradiation reached the interface between the W film and substrate, where NRA showed enhanced retention of oxygen. At that depth, two times higher D concentration was observed compared to D concentration in the damaged area in the middle of the film indicating on defect stabilization due to the presence of oxygen.